2022
DOI: 10.3390/ma15041355
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Mix Proportion and Aggregate Features on the Performance of Eco-Efficient Fine Recycled Concrete Aggregate Mixtures

Abstract: Most of the previous research on recycled concrete aggregates (RCA) has focused on coarse RCA (CRCA), while much less has been accomplished on the use of fine RCA particles (FRCA). Furthermore, most RCA research disregards its unique microstructure, and thus the inferior performance of concrete incorporating RCA is often reported in the fresh and hardened states. To improve the overall behaviour of RCA concrete advanced mix design techniques such as equivalent volume (EV) or particle packing models (PPMs) may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…However, in both cases the use of recycled aggregate is valid. In addition, [11] mentions that the results of his background suggest that the recycled mixtures that contain 100% Residue can produce 35% more drying shrinkage along with 30% and 50% less compressive strength.…”
Section: Discussionmentioning
confidence: 99%
“…However, in both cases the use of recycled aggregate is valid. In addition, [11] mentions that the results of his background suggest that the recycled mixtures that contain 100% Residue can produce 35% more drying shrinkage along with 30% and 50% less compressive strength.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, work has shown that the EV method produces suitable concrete despite the type of RCA used [11]. Furthermore, the EV method was further used while incorporating FRCA which showed an overall better performance compared to using the DRM [12][13][14]. Figure 2, therefore, illustrates the volumetric comparison of concrete proportioned through the EV method using CRCA and FRCA along with its companion CC.…”
Section: Mix-design Methods Using Rcamentioning
confidence: 99%
“…Previous studies on concrete made with CRCA show that the higher the RM content, the lower the RCA concrete mechanical properties for mixtures proportioned with the DRM [20][21][22][23][24][25][26] yet, the quality of the RM also plays an important role in the recycled concrete's mechanical properties [10]. Moreover, recent studies have been conducted to improve and evaluate the performance of concrete made with FRCA [12][13][14]27]. Indeed, the multi-phase nature of FRCA is influenced by its crushing procedure where a more severe crushing sequence results in a lower RCP content which in turn influences the concrete's properties and performance.…”
Section: Recycled Concrete Aggregates (Rca)mentioning
confidence: 99%
See 2 more Smart Citations